Efficacy and factors related to prognosis of combination chemotherapy with different radiotherapy methods in patients with unresectable hepatocellular carcinoma - Lian-Qiang Han (Scientific Reports)
Abstract Apart from beam radiation (BR), treatment with radioactive implants (RI) was another important modality of cancer therapy. The main purpose was to explore which radiotherapy combined with chemotherapy was more beneficial and identify factor related to prognosis for patients with unresectable hepatocellular carcinoma (HCC). Patients were collected from the surveillance, epidemiology, and end results (SEER) database and were divided into RI group and BR group. Overall survival (OS) and HCC-specific survival were compared between two groups. Propensity score matched (PSM) was used to reduce baseline differences between the two groups. Univariate and multivariate Cox analysis were used to determine the factors affecting the prognosis, and a nomogram model was constructed based on independent risk factors. A total of 1481 HCC patients from 2000 to 2019 were enrolled, including 502 in RI group and 979 in BR group. After PSM, 376 pairs of matched cases were selected. In the matched cohort, there was no significant difference in the median OS (RI vs. BR, 15 vs. 17 months, P = 0.616) and HCC-specific survival (RI vs. BR, 18 vs. 21 months, P = 0.154) between the two groups. Subgroup analysis of different stages also showed no significant difference. Multivariate Cox analysis also did not indicate a significant prognostic difference between the two groups. Based on the independent risk factors of OS such as AFP, grade, TNM staging, and M1, a nomogram model was constructed and verified. When combined with chemotherapy in the treatment of unresectable HCC, RI demonstrated comparable prognostic outcomes to BR, suggesting its potential as an alternative treatment option. In addition, the constructed nomogram model might be able to intuitively and accurately predict the prognosis of unresectable HCC patients receiving chemotherapy combined with radiotherapy.